Faith-Based Organizations and Health Empowerment of The Needy in Kitunga Sub-County Ntungamo District. - Tusiime, Cresent (Kabale University, 2024)
Faith-based organizations are a vital part of society, providing a substantial portion of care in developing countries, often reaching vulnerable populations living under adverse conditions. There is therefore a need to recognize them as essential contributors to universal health access effort. FBOs have for a long time committedly made positive contributions towards the provision of education, support in agriculture, skills, and health to enhance social welfare but some people in rural areas still have low income, poor health standards, no food security, and limited skills and lack employment due to low levels of education hence poor social welfare. It was against this background that this study was conducted to assess the effect of faith-based organizations and health empowerment of the needy in the Kitunga sub-county. The general objective of the study was to assess the Faith-Based Organizations and Health Empowerment of the needy in the Kitunga sub-county. The general objective of the study assess the Faith-Based Organizations and Health Empowerment of the needy in the Kitunga sub-county.